The Mediating Role of Satisfaction in the Impact of Ease of Use, Service Features, and Trust on User Loyalty in Zoom.: Peran Mediasi Kepuasan dalam Pengaruh Kemudahan Penggunaan, Fitur Layanan, dan Kepercayaan terhadap Loyalitas Pengguna di Zoom. - Rudi Cahyono; Dewi Komala Sari (Universitas Muhammadiyah Sidoarjo, 2022)
This quantitative study investigates the relationship between ease of use, service features, trust, user satisfaction, and loyalty in the context of the Zoom application. A non-probability sampling method was employed, and data were collected from 100 respondents who were students of the Muhammadiyah University of Sidoarjo management program and had prior experience using Zoom. Path analysis using the Smart PLS version 3.0 program was conducted for data analysis. The findings reveal that ease of use does not significantly influence user loyalty, while service features and trust positively affect user loyalty. Additionally, ease of use and trust have a positive impact on user satisfaction, while service features do not significantly affect user satisfaction. Furthermore, the study demonstrates that ease of use and trust indirectly influence user loyalty through satisfaction, whereas service features do not exert an indirect effect on user loyalty through satisfaction. These results provide valuable insights for both researchers and practitioners in understanding the factors that drive user loyalty in video conferencing applications, with implications for improving user experience and service quality. Highlights: Ease of use and trust significantly impact user loyalty in Zoom. Service features do not directly affect user loyalty but play a role in shaping user satisfaction. User satisfaction mediates the relationship between ease of use, trust, and user loyalty in the Zoom application. Keywords: Zoom, user loyalty, ease of use, service features, trust.